2020
DOI: 10.1002/srin.202000191
|View full text |Cite
|
Sign up to set email alerts
|

The RecoDust Process—Upscale of a Pilot Plant

Abstract: The RecoDust process is a pyrometallurgical approach for the treatment of heavy metal–containing basic oxygen furnace dusts (BOFD) and delivers two products without any residues: the iron rich RecoDust slag and a zinc rich filter dust, called crude zinc oxide (CZO). The state of the art Waelz process has some disadvantages and is only suitable for dusts with zinc contents >15%. Within the frame of a project of the Austrian competence center program K1‐MET and with financial support of voestalpine Stahl, a Reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The process is funded within the Austrian COMET program K1-MET and is currently in the pilot plant stage (300 kg/h throughput) and transfers the iron content into a slag phase to be used as a secondary iron resource for the sintering plant or the BF. The zinc content in this product stays below 0.5 wt.% [19][20][21]. The crude zinc oxide, which is separated with a bag filter (representing the second product), is treated using a leaching step and shows a low halide content (chlorine and fluorine~0.1 wt.% each).…”
Section: Pyrometallurgical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The process is funded within the Austrian COMET program K1-MET and is currently in the pilot plant stage (300 kg/h throughput) and transfers the iron content into a slag phase to be used as a secondary iron resource for the sintering plant or the BF. The zinc content in this product stays below 0.5 wt.% [19][20][21]. The crude zinc oxide, which is separated with a bag filter (representing the second product), is treated using a leaching step and shows a low halide content (chlorine and fluorine~0.1 wt.% each).…”
Section: Pyrometallurgical Processesmentioning
confidence: 99%
“…With upscaling to 1000 kg/h being the current focus of the development project, a new pneumatic conveying system was installed; it uses natural gas as the conveying medium. The main benefit of RecoDust is that no carbonaceous solid reducing agents are required since the reducing atmosphere is only adjusted via the natural gas/oxygen flame [19][20][21].…”
Section: Pyrometallurgical Processesmentioning
confidence: 99%
“…In the trials shown here, the zinc content of the RDS equaling to 0.4 wt.% demonstrated the ability that RecoDust can produce an Fe-rich product with enough quality for an internal recycling as secondary iron source. The 0.4 wt.% zinc is much lower than that of the commissioning phase of the pneumatic conveying system (when starting the pneumatic conveying system, zinc content of 3.1 wt.% was obtained in the RDS) [25]. This low zinc content now being obtained in the RDS is due to the stable uniform dust dosing rate managed by the pneumatic conveying system.…”
Section: Discussionmentioning
confidence: 86%
“…Zinc can be obtained from zinc ferrite by acid leaching under elevated pressure 9 or using pyrometallurgical processes, such as the Waelz kiln process and its modification and the RecoDust process based on the reduction of heavy metal-containing basic oxygen furnace dust by H 2 and CO, as described in 10 and 11 , respectively. Pickles 12 investigated the selective reduction by iron, reporting an optimal temperature and pressure range for zinc and lead recovery.…”
mentioning
confidence: 99%